If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3p + 8 = 5 + -7p + 4 Reorder the terms: 8 + -3p = 5 + -7p + 4 Reorder the terms: 8 + -3p = 5 + 4 + -7p Combine like terms: 5 + 4 = 9 8 + -3p = 9 + -7p Solving 8 + -3p = 9 + -7p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '7p' to each side of the equation. 8 + -3p + 7p = 9 + -7p + 7p Combine like terms: -3p + 7p = 4p 8 + 4p = 9 + -7p + 7p Combine like terms: -7p + 7p = 0 8 + 4p = 9 + 0 8 + 4p = 9 Add '-8' to each side of the equation. 8 + -8 + 4p = 9 + -8 Combine like terms: 8 + -8 = 0 0 + 4p = 9 + -8 4p = 9 + -8 Combine like terms: 9 + -8 = 1 4p = 1 Divide each side by '4'. p = 0.25 Simplifying p = 0.25
| k^4+7k^3-30k^2= | | 22=8m+3m | | -78p+2p-5p+8+48= | | 3f-2g=7+hforg | | 3x-5=10-5x | | 2z+(-10)=-19 | | y/1-3/4 | | 11y-36+63= | | -5x-x=6 | | -9(5r-3s)= | | x=7(176)-x | | ak^2-11ak+18a= | | 5m-5=-2+5+9m | | X+bc=5 | | 9x^3=10 | | 4x-17+137= | | 2.1=x/2 | | 3(x-4)+8x=19-2(x+3) | | -7/11x=-2 | | 2-(x-1)=5x+9 | | 8k^3-162k= | | 38-g=34 | | 1/3-7=4 | | 4x+45+5x-18= | | -(2s+7)+3(2s+5)-2s= | | -4(4y-7)-y=-3(y-3) | | K-5= | | 8x-6x-4x=12 | | 112=5(6n-2)+2 | | 5m-5=9m+5 | | 12x-14x=12 | | 6y3/2 |